A figuração poético-alegórica da morte em as meninas, de Lygia Fagundes Telles - Santos, Maria das Dores Pereira (2006)
The objective of this dissertation is to track the ways poetical death is constructed in the novel As Meninas, by Lygia Fagundes Telles. The interest for this theme resulted from recognizing homologous aspects in the literary text and the military dictatorship context internal to lygian writing. The analysis is guided by the artisticliterary procedures of poetical death construction using the concept of modern allegory systemized by Walter Benjamin. The concept of allegory as an expression that articulates the synthesis between social crisis and artistic creation shows the condition of a romantic language built by the fragmented, evasive, and traumatizing perception of existence. To illustrate these procedures, the study focused on the structural aspects of the language, such as character, time and speech. The guiding hypothesis throughout the reading was that these aspects configure a fragmented poetry, designed using the construction/ruin paradox. The conclusion of this study is that these procedures articulate, in the novel, a neo-baroque effect on the image of death and puts forth questions related to the crisis of the narrative and of the post modern individual